1996
DOI: 10.1007/bf00175219
|View full text |Cite
|
Sign up to set email alerts
|

Serum haemolytic and agglutinating activity as indicators of fish immunocompetence: their suitability in stress and dietary studies

Abstract: Gilthead sea bream, Sparus aurata, were subjected to different stressful situations and the haemolytic activity mediated by the alternative complement and the agglutinating serum activity were tested as indicators of immunocompetence. The results show that both parameters were significantly compromised after chronic or repeated acute stress as well as in groups fed with vitamin E or o)3 highly unsaturated fatty acids (HUFA) deficient diets and in infected fish. These results suggest that both haemolytic and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 22 publications
5
67
0
3
Order By: Relevance
“…In other teleosts, such as Sparus aurata [8,55,56], Salmo trutta [6] and Oreochromis niloticus [57] the same time period is sufficient to observe a return to normality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other teleosts, such as Sparus aurata [8,55,56], Salmo trutta [6] and Oreochromis niloticus [57] the same time period is sufficient to observe a return to normality.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the haemagglutinating activity, agglutinins are recognised to be a key component of innate immune system in many fish species, which are active against homologous or heterologous red blood cells [8,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating leucocyte counts, often used as a parameter to assess the immunological health of fish, have been shown here not to accurately reflect the real health status of the fish because circulating levels of leucocytes are maintained by the immunological organs. Other studies in our laboratory have shown that in gilthead sea bream differences in circulating lymphocyte numbers were noted between 3 and 9 d after acute or chronic disturbance (Sufier & Tort 1995, Suner et al 1995, Tort et al 1996.…”
Section: Discussionmentioning
confidence: 79%
“…Mean corpuscular hemoglobin content (MCHC) was calculated according to the formula: MCHC = Hb (g/dl)/ Hk. Plasma from these fresh blood samples was used to analyze alternative complement activity (ACH50) following Tort et al (1996). Plasma from the remaining five blood samples from each tank were used in the lysozyme analysis following the procedures of Hutchinson and Manning (1996) and Magnadottir et al (1999).…”
Section: Feeding and Monitoringmentioning
confidence: 99%